Editorial: Critical Research in and through Practice - Nduna, Mzikazi; Mthombeni, Andile (PINS-Psychology in Society, 2021)
Since the call for the special issue back in 2016, various life altering events have taken place, including the Covid-19 pandemic that South Africa and many other nations across the globe find themselves battling with. The pandemic has had an impact on how we do things, including how we conduct research, particularly qualitative research that is more often than usual reliant on face-to-face interactions: observations, interviews and/or discussions. We now see a move towards online platforms in conducting qualitative research due to social distancing public health measures and lockdown restrictions to reduce the spread of the novel Corona virus that causes Covid-19. The new norm is quickly changing the way we think about qualitative research methods and designs. Furthermore, 2019 was a year where we witnessed race science research methods being challenged as a result of two journal publications from the Universities of Stellenbosch and Cape Town resulting in a retraction and staff resignation, respectively. The challenges were not only posed to the authors but to the university’s ethics committees and the journals that published the biased, un-scientific content with racist ideological underpinnings. This brought into the fore the importance of critical scholarship.